Mineral nutrition of higher plants - Marschner, Horst (Academic Press, 1995)
An understanding of the mineral nutrition of plants is of fundamental importance in both basic and applied plant sciences. The Second Edition of this book retains the aim of the first in presenting the principles of mineral nutrition in the light of current advances. This volume retains the structure of the first edition, being divided into two parts: Nutritional Physiology and Soil-Plant Relationships. In Part I, more emphasis has been placed on root-shoot interactions, stress physiology, water relations, and functions of micronutrients. In view of the worldwide increasing interest in plant-soil interactions, Part II has been considerably altered and extended, particularly on the effects of external and interal factors on root growth and chapter 15 on the root-soil interface. The second edition will be invaluable to both advanced students and researchers. Key Features * Second Edition of this established text * Structure of the book remains the same * 50% of the reference and 50% of the figures and tables have been replaced * Whole of the text has been revised * Coverage of plant (soil interactions has been increased considerably).